An Early–Life Stage Alternative Testing Strategy for Assessing the Impacts of Environmental Chemicals in Birds. (27th December 2019) - Farhat, Amani; Crump, Doug; Bidinosti, Lisa; Boulanger, Emily; Basu, Nil; Hecker, Markus; Head, Jessica A.
Abstract: Early–life stage (ELS) toxicity tests are recognized as an advancement over current testing methodologies in terms of cost, animal use, and biological relevance. However, standardized ELS tests are not presently available for some vertebrate taxa, including birds. The present study describes a Japanese quail ( Coturnix japonica ) ELS test that is a promising candidate for standardization and applies it to test 8 environmental chemicals (ethinylestradiol, benzo[ a ]pyrene, chlorpyrifos, fluoxetine, lead(II)nitrate, trenbolone, seleno‐L‐methionine, hexabromocyclododecane). Individual chemicals were injected into the air cell of unincubated Japanese quail eggs at 3 concentrations, all predicted to cause ≤20% mortality. Survival to embryonic day 16 was consistently high (>90%) among the vehicle‐injected controls. All chemicals, except ethinylestradiol, were detected in liver tissue, most at concentrations suggestive of embryonic clearance. Adverse effects were observed for 5 of the 8 chemicals; chlorpyrifos (41.1 µg/g) significantly increased developmental abnormalities and decreased embryo and gallbladder mass. Ethinylestradiol (54.2 µg/g) and hexabromocyclododecane (0.02 µg/g) decreased embryo mass and tarsus length, respectively. Benzo[ a ]pyrene (0.83 µg/g) and fluoxetine hydrochloride (32.7 µg/g) exceeded the 20% mortality cutoff. No effects were observed following lead(II)nitrate, seleno‐L‐methionine, or trenbolone exposure up to 10.7, 0.07, and 4.4 µg/g, respectively. Overall, our ELS approach was time‐ and cost‐effective, caused minimal mortality in controls, effectively delivered diverse chemicals to the embryo, and permitted identification of apical outcomes, all of which provide support toward standardization. Environ Toxicol Chem 2019;39:141–154. © 2019 SETAC